Need for inclusion of non-conventional medicine teaching in conventional medicine programs for the South American region - Salazar-Granara, Alberto (2022)
The World Health Organization (WHO) is an institution that represents conventional or allopathic medicine (1) and has produced a series of documents compiling the state of the art of non-conventional medicine (traditional medicine or TM) in its Member States.